Prediction of Premature Outflow of Amniotic Fluid in Preterm Pregnancy - Nargiz Nuralievna, Shavazi; Nodira Islamovna, Zakirova; Dildora Rakhimovna, Khudoyarova (International Journal of Psychosocial Rehabilitation, 2020)
Premature discharge of amniotic fluid is a complication of pregnancy, characterized by a violation of the integrity of the membranes of the fetus and the discharge of amniotic fluid before labor, regardless of gestational age. The aim of the study is to develop optimal methods for predicting the threat of premature outflow of amniotic fluid in pregnant women. A total of 478 pregnant women were examined to assess risk factors for the development of premature amniotic fluid flow. Retrospectively analyzed 350 stories of pregnant women from 2016 to 2019. Prospectively, under our supervision, there were 128 pregnant women. The main group consisted of 93 pregnant women. The control group consisted of 35 women. All birth histories were studied, and risk factors leading to this pathology were identified. Prospective analysis. We identified risk factors such as stress, bad habits, age, abortion, gynecological diseases, the threat of abortion, and premature discharge of amniotic fluid. We have developed a prognostic matrix according to the anamnesis and clinical symptoms, using the method of normalizing intensive indicators E.N. Shigan. According to this indicator, the computer program was created on January 25, 2019 (Intellectual Property Agency under the Ministry of Justice of the Republic of Uzbekistan, No. DGU 06117). "A program for identifying risk factors in case of the threat of premature discharge of amniotic fluid." We identified and divided pregnant women into 3 groups: The first group included (n = 17) pregnant women with a low probability of premature discharge of amniotic fluid, group 2 (n = 31) had an average probability of an outflow, and group 3 (n = 45) had a high risk. The results of our studies showed that diene conjugates were 2.2 times higher than normal, and malondialdehydes were 1.4 times higher, which certainly can be one of the pathogenetic factors in the thinning of the amniotic membranes, leading to their failure. Based on the foregoing, we also studied the functional state of the endothelium, a 1.3-fold increase in thrombomodulin content, a 1.5-fold increase in von Willebrand factor, a 2.1-fold increase in fibronectin, a 1.3-fold increase in soluble cell adhesion molecules, and a 1.3-fold increase in vascular cell adhesion molecule 1.1 times. From the cytokine status, a significant increase in the content of proinflammatory cytokines was detected: interleukin 2.9 times, tumor necrosis factor 2.6 times, C-3 1.9 times, and C-4 2.0 times in patients at risk of developing premature amniotic fluid outflow in comparison with the control group. An important role in the remodeling of the intercellular space of blood vessels is played by matrix metalloproteinases. A significant increase in the content of MMP-1 as the main enzyme was 2.5 times, MMP-3 was 4.9 times, MMP-9 was 1.5 times, and the concentration of TIMP-1 was 0.8 times lower compared to the control group. Another indicator may be the indicator of fetal fibronectin determined in the vaginal secretion, which in 66% of cases was positive.